Association of Phytophthora with Declining Vegetation in an Urban Forest Environment - Mohammed Y. Khdiar; Paul A. Barber; Giles E. StJ. Hardy; Chris Shaw; Emma J. Steel; Cameron McMains; Treena I. Burgess (Microorganisms, 2020)
Urban forests consist of various environments from intensely managed spaces to conservation areas and are often reservoirs of a diverse range of invasive pathogens due to their introduction through the nursery trade. Pathogens are likely to persist because the urban forest contains a mixture of native and exotic plant species, and the environmental conditions are often less than ideal for the trees. To test the impact of different land management approaches on the Phytophthora community, 236 discrete soil and root samples were collected from declining trees in 91 parks and nature reserves in Joondalup, Western Australia (WA). Sampling targeted an extensive variety of declining native trees and shrubs, from families known to be susceptible to Phytophthora. A sub-sample was set aside and DNA extracted for metabarcoding using Phytophthora-specific primers; the remaining soil and root sample was baited for the isolation of Phytophthora. We considered the effect on the Phytophthora community of park class and area, soil family, and the change in canopy cover or health as determined through sequential measurements using remote sensing. Of the 236 samples, baiting techniques detected Phytophthora species from 24 samples (18 parks), while metabarcoding detected Phytophthora from 168 samples (64 parks). Overall, forty-four Phytophthora phylotypes were detected. Considering only sampling sites where Phytophthora was detected, species richness averaged 5.82 (range 1–21) for samples and 9.23 (range 2–24) for parks. Phytophthora multivora was the most frequently found species followed by P. arenaria, P. amnicola and P. cinnamomi. While park area and canopy cover had a significant effect on Phytophthora community the R2 values were very low, indicating they have had little effect in shaping the community. Phytophthora cinnamomi and P. multivora, the two most invasive species, often co-occurring (61% of samples); however, the communities with P. multivora were more common than those with P. cinnamomi, reflecting observations over the past decade of the increasing importance of P. multivora as a pathogen in the urban environment.